Illegal immigration and commercial sex - Williams, Phil, 1948- (Portland, Ore : Frank Cass, 1999)
"This volume examines the dynamics of the sex slave trade in both Europe and Asia, identifies the role of organized crime, and considers the counter-measures which governments and law enforcement agencies must take to combat this global problem."--Jacket
Human commodity trafficking: an overview / Phil Williams -- Illegal migration: personal tragedies, social problems, or national security threats? / Margaret E. Beare -- Capitalizing on transition economies: the role of the Russian mafiya in trafficking women for forced prostitution / Gillian Caldwell, Steve Galster, Jyothi Kanics and Nadia Steinzor -- Trafficking in people in Thailand / Pasuk Phongpaichit -- Organized crime and trafficking in women from Eastern Europe in the Netherlands / Gerben J.N. Bruinsma and Guus Meershoek -- Prostitution and the mafia: the involvement of organized crime in the global sex trade / Sarah Shannon -- Trafficking in women and children: a market perspective / Phil Williams -- Child pornography in the digital age / Anna Grant, Fiona David, and Peter Grabosky -- The fusion of immigration and crime in the European Union: problems of cooperation and the fight against the trafficking in women / Penelope Turnbull -- Memorandum for the Secretary of State, the Attorney General, the Administrator of the Agency for International Development, the Director of the United States Information Agency -- March 11, 1998 / William J. Clinton -- October 1996 Report -- presented to the UN General Assembly : note / by the Secretary-General -- World Congress Against the Commercial Sexual Exploitation of Children -- Provisional report of the congress / General Rapporteur Professor Vitit Muntarbhorn.
Includes bibliographical references.
Keywords: Transnational crime; Organized crime; Sex crimes; Smuggling; Emigration and immigration; Illegal immigration; Sex Offenses; Emigration and Immigration; Crimes sexuels; Immigration clandestine; Organized crime; Prostitution; Kindermishandeling